2010
DOI: 10.1002/hep.23936
|View full text |Cite
|
Sign up to set email alerts
|

The immunoregulatory role of CD244 in chronic hepatitis B infection and its inhibitory potential on virus-specific CD8+ T-cell function

Abstract: Multiple inhibitory receptors may play a role in the weak or absent CD81 T-cell response in chronic hepatitis B virus (HBV) infection. Yet few receptors have been characterized in detail and little is known about their complex regulation. In the present study, we investigated the role of the signaling lymphocyte activation molecule (SLAM)-related receptor CD244 and of programmed death 1 (PD-1) in HBV infection in 15 acutely and 66 chronically infected patients as well as 9 resolvers and 21 healthy controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(179 citation statements)
references
References 28 publications
(32 reference statements)
4
171
2
Order By: Relevance
“…14,44 Persistent HBV infection impairs HBV-specific CD8 1 T-cell function and results in the exhausted-phenotype CD8 1 cells that fail to clear virus. 45,46 In our study, our results demonstrate that blockage of TNF-a leads to increasing liver-infiltrating PD-1 high CD127 low -exhausted phenotype CD8 1 T cells in mice with HBV persistence. These results indicate that in HBV persistence, blockage of TNF-a will further impair the adaptive immune response and that TNF-a is crucial for maintaining an effective anti-HBV immune response.…”
Section: Discussionsupporting
confidence: 55%
“…14,44 Persistent HBV infection impairs HBV-specific CD8 1 T-cell function and results in the exhausted-phenotype CD8 1 cells that fail to clear virus. 45,46 In our study, our results demonstrate that blockage of TNF-a leads to increasing liver-infiltrating PD-1 high CD127 low -exhausted phenotype CD8 1 T cells in mice with HBV persistence. These results indicate that in HBV persistence, blockage of TNF-a will further impair the adaptive immune response and that TNF-a is crucial for maintaining an effective anti-HBV immune response.…”
Section: Discussionsupporting
confidence: 55%
“…It has recently been shown that CD244 is expressed on virus-specific CD8 + T cells (9,(39)(40)(41) and that CD244 signaling correlates with viral persistence of hepatitis B virus (HBV) and HCV in humans (9,39,40). However, little is known about the molecular mechanism and consequence for CD244 regulation of T-cell effector functions during active TB infection.…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%
“…15 Tregs, demarcated by CD4 + CD24 + FoxP3 + expression, 16 inhibit effective virus-specific immune responses 17,18 and can also express programmed death receptor-1 (PD-1), which further deters immune responses when expressed on CD4 + , CD8 + , NK T cells, monocytes, or B cells. [19][20][21][22][23] In this study, we investigated the immunoregulatory mechanisms that suppress HBV-specific immunity in HIV-positive and HIVnegative CHB patients and explored methods to augment the HBV-specific immune response thereby enhancing the potential for HBV eradication.…”
Section: Introductionmentioning
confidence: 99%